(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To develop and evaluate the reliability, content validity, and exploratory factor structure of a scale measuring parents’ knowledge, attitudes, and perceived behavioral control toward dengue vaccination for their children. Method: A cross-sectional study was conducted among 253 parents of primary school children in Ho Chi Minh city in 2025. The questionnaire, consisting of three subscales, was developed based on health behavior theories. Content validity was assessed using the item- and scale-level Content Validity Index (I-CVI, S-CVI) and Cohen’s Kappa (K). Internal consistency was measured by Cronbach’s Alpha, and construct validity was examined using exploratory factor analysis. Results: Of the participants, 65.4% reported an intention to vaccinate their children against dengue. All subscales demonstrated satisfactory content validity and reliability (Cronbach’s Alpha: 0.70-0.89). Exploratory factor analysis indicated adequate sampling adequacy (KMO ≥ 0.69; Bartlett’s test, p < 0.001). The variance explained was 23.6% for knowledge, 58.4% for attitude, and 44.6% for perceived behavioral control, with factor loadings ranging from 0.36 to 0.84. Higher scores in knowledge, attitude, and perceived behavioral control were significantly associated with stronger intention to vaccinate (p < 0.05). Conclusion: The developed scale showed good reliability and validity and can be applied in community-based studies to identify factors influencing parents’ intention to vaccinate their children against Dengue